Effects of NT-814, a dual neurokinin 1 and 3 receptor antagonist, on vasomotor symptoms in postmenopausal women: a placebo-controlled, randomized trial. Issue 5 (May 2020) - Trower, Mike; Anderson, Richard A.; Ballantyne, Elizabeth; Joffe, Hadine; Kerr, Mary; Pawsey, Steve
Abstract: Objectives: To evaluate the safety, pharmacokinetics, and preliminary efficacy of NT-814, a dual neurokinin 1, 3 antagonist, in postmenopausal women with vasomotor symptoms (hot flashes). Methods: We completed a double-blind, randomized, placebo-controlled trial in three US clinical research units in 76 postmenopausal women with moderate/severe hot flashes. Participants were randomized to 14 days of once-daily NT-814 or placebo within each of four sequential dose cohorts; 50, 100, 150, and 300 mg. Participants completed diaries of hot flash frequency and severity and waking due to night sweats before (baseline) and during treatment. Results: All prespecified efficacy parameters (24-h hot flash frequency and severity, frequency of waking due to night sweats) decreased in all groups (including placebo). Mean reduction from baseline at week 2 in moderate/severe hot flash frequency was 37% in the placebo group and, respectively, 24% ( P  = 0.048 vs placebo), 59% ( P  = 0.155), 84% ( P  < 0.001) and 66% ( P  = 0.022) in the 50 mg, 100 mg, 150 mg, and 300 mg NT-814 groups; in waking due to night sweats reduction was 20% ( P  = 0.059), 55% ( P  = 0.135), 81% ( P  < 0.001), and 63% ( P  = 0.031) in the NT-814 groups and 32% in the placebo group. The improvement with NT-814 ≥150 mg was also evident in the first week of treatment. The most common treatment-related adverse events were mild somnolence and headache, more frequently in the 300 mg group. Safety monitoring identified no concerns. Conclusions: Once-daily NT-814 (≥150 mg/d) resulted in a rapid, marked improvement in hot flashes and waking due to night sweats. No safety concerns were identified. Doses up to 300 mg were well tolerated.